High-Content Screening Microscopy Identifies Novel Proteins With a Putative Role in Secretory Membrane Traffic - Starkuviene, Vytaute; Liebel, Urban; Simpson, Jeremy C.; Erfle, Holger; Poustka, Annemarie; Wiemann, Stefan; Pepperkok, Rainer

(untitled) (Genome Research, 2004)
Here we describe the establishment of microscope-based functional screening assays in intact cells that allow us to systematically identify new proteins involved in secretory membrane traffic, and proteins that can influence the integrity of the Golgi complex. We were able to identify 20 new proteins that affected either secretory transport, Golgi morphology, or both, when overexpressed in cells. Control experiments with human orthologs to yeast proteins with a role in membrane traffic, or already well characterized mammalian regulators of the secretory pathway, confirmed the specificity and significance of our results. Proteins localized to the Golgi complex or endoplasmic reticulum (ER) showed preferential interference in our assays. Bioinformatic analysis of the new proteins interfering with membrane traffic and/or Golgi integrity revealed broad functional variety, but demonstrated a bias towards proteins with predicted coiled-coil domains and repeat structures. Extending our approach to a much larger set of novel proteins in the future will be an important step toward a more comprehensive understanding of the molecular basis of the secretory pathway. It will also serve as an example for similar microscope-based screens addressing different biological questions.